2017
DOI: 10.20960/nh.1000
|View full text |Cite
|
Sign up to set email alerts
|

Biomarcadores de pronóstico modificables nutricionalmente en el paciente con cáncer colorrectal tras el diagnóstico de la enfermedad

Abstract: Introduction: Colorectal cancer (CRC) is the second most common cancer in the Western world. About one million of new CRC cases are diagnosed per year. The survival rate of patients with CRC changes widely, even among patients with the same tumor histology. This is possibly due to the impact of environmental factors on tumor development. The diet is the most important among these factors. It is known that nutrition can modify the risk of CRC. However, the role that nutrition plays in the risk of recurrence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…29,33 Therefore, need-based education should be provided to these survivors, their families, and their family caregivers. Moreover, findings showed that health responsibility improves disease prognosis, 39,40,42 reduces the likelihood of recurrence, increases survival rate, and improves quality of life. 17,18,[40][41][42] A study reported that compared with CRC survivors who referred to oncology specialists, those who referred to general physicians were three times more likely to experience cancer-related complications and did not refer to healthcare providers for the second time to analyze the results of their laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,33 Therefore, need-based education should be provided to these survivors, their families, and their family caregivers. Moreover, findings showed that health responsibility improves disease prognosis, 39,40,42 reduces the likelihood of recurrence, increases survival rate, and improves quality of life. 17,18,[40][41][42] A study reported that compared with CRC survivors who referred to oncology specialists, those who referred to general physicians were three times more likely to experience cancer-related complications and did not refer to healthcare providers for the second time to analyze the results of their laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…17,42 This highlights the importance of providing these patients and their families with quality education in order to encourage their engagement in self-care and promote their communication with healthcare providers 27 ; otherwise, they may seek health information from unreliable sources which may result in the acquisition of misleading and contradictory information about healthy eating, physical activity, and self-care, delayed recovery, and disease recurrence. 39 Respecting alcohol consumption, some studies reported no significant relationship between alcohol consumption and overall and CRC-related death rates, 40,43 while some studies recommended alcohol abstinence effective in preventing CRC recurrence. 30,40 Smoking in CRC survivors increases the risk of cardiovascular disease, respiratory disease, lung cancer, CRC mortality, and overall mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation